Recovering Erased and Obliterated Marks on High Strength Aluminum Alloy Surfaces by Etching Technique - Bong Yeu, Uei (Universiti Sains Malaysia, 2009)
The current study describes the results of the experiments conducted on restoration of erased and obliterated marks on high strength aluminum alloy surfaces. The use of this alloy is on increase in the field of vehicle and firearm manufacturing. Serial numbers imprinted on these items are removed by criminals for several reasons. Recovering these erased or obliterated numbers is necessary in the solution of criminal cases. Hence, a series of experiments was designed to identify the sensitivity and efficacy of some of the metallographic reagents which could be used to recover marks on these surfaces. The work consisted of preparing several high strength aluminum alloy plates and engraving marks on them using a computer controlled engraving machine "Gravograph". The marks were then erased to different levels down to the depth of the engraving. Five etching reagents were applied on the erased plates by either swabbing or immersion method to test their sensitivity and reproducibility. The results have shown that reagents i) 60 % HCl and 40 % NaOH and ii) 10 %phosphoric acid were able to produce good results, which were also reproducible. Experiments were also performed by erasing the engraved marks until the marks were totally removed and later the erased area was over-engraved with some new marks. Also, experiments of obliteration of the original marks by centre-punching were conducted. In both cases of over-engraving and obliteration the above two reagents were successful to bring back the original numbers.